Necrotizing Fasciitis as a Complication of Odontogenic Abscess - Giselle, Juárez-Rebollar Alejandra; Daniel, Juárez-Rebollar; Marcelo, Juárez-Paredes Celso (Highlights on Medicine and Medical Science Vol. 1, 2021)
Different dental infections can get complicated and spread. Necrotizing fasciitis is a rare infection, which occurs mainly in immunocompromised patients, and usually presents as a serious complication of dental infections, compromising the general condition of the patient and can even be life-threatening. It requires rapid recognition of the clinic to be able to diagnose it, as well as the support of imaging studies to ascertain the limits of affection caused by Necrotizing Fasciitis. The management for necrotizing fasciitis is medical (broad spectrum antibiotics and multidisciplinary management) as well as extensive and aggressive surgery. The importance of knowing Necrotizing Fasciitis will help to provide better care to patients, improve prognosis, act on time and limit the disease. That is why it requires knowledge and emergency management. The following text explains in detail Odontogenic Necrotizing Fasciitis.